Association between arterial stiffness and orthostatic hypotension: A systematic review and meta-analysis - Saz-Lara, Alicia; Cavero-Redondo, Iván; Martínez-Vizcaíno, Vicente; Lucerón-Lucas-Torres, Maribel; Pascual-Morena, Carlos; Sequí-Domínguez, Irese (Frontiers in Physiology, 2023)
Background. Orthostatic hypotension, defined as a decrease in blood pressure on standing, is associated with an increased risk of mortality and cardiovascular events in the general population. In addition, it has recently been suggested that arterial stiffness is independently associated with orthostatic hypotension, which may be due to a loss of the buffering effect of the ascending aorta and an early return of pressure waves. However, the specific mechanisms underlying this association remain unclear. Thus, we aimed to evaluate the association between orthostatic hypotension and arterial stiffness in the adult population. Methods. The PubMed, Scopus, Web of Science, and Cochrane Library databases were searched from inception to January 31, 2022. The DerSimonian and Laird method was used to calculate pooled odds ratio (OR) estimates and their respective 95% confidence intervals (95% CI) for the association between orthostatic hypotension and arterial stiffness. Results. Overall, 11 studies were included, with a total of 10611 subjects. Our results showed that increased arterial stiffness raises the risk of orthostatic hypotension (OR: 1.40, 95% CI: 1.28-1.54), with a stronger association at central arterial stiffness (OR: 1.50, 95% CI: 1.34-1.68) than at peripheral arterial stiffness (OR: 1.29, 95% CI: 1.17-1.43). Conclusion. Our findings showed that increased arterial stiffness raises the risk of orthostatic hypotension by 40% among the adult population. Considering that orthostatic hypotension, which is usually a consequence of antihypertensive treatment, has been widely associated with the risk of cardiovascular events, appropriate control of arterial stiffness could be a clinical strategy to prevent cardiovascular morbidity and mortality.